Practicality of Problem-Based Physics Learning Tools with Video Assistance to Improve Problem-Solving Ability of Students - Susilawati Susilawati; Fiki Rahmana; Kosim Kosim; Lalu Muliyadi (Journal of Science and Science Education, 2022)
This study aims to produce problem-based physics learning tools with the help of videos that practically improve the problem solving abilities of students. The research design used is a 4D model consisting of define, design, develop and disseminate. The learning tools developed are syllabus, lesson plan, student worksheets, videos, and problem solving ability questions. The finished learning tools were then tested in a limited way in class XI MIPA 7 SMAN 1 Mataram to find out the practicality of these devices. The results showed that the device, on average, received a positive response from students and teachers. This can be seen from the responses "agree" and "strongly agree" for each component of the questionnaire given by students and teachers. Based on these data, it can be concluded that problem-based physics learning tools with the help of videos, practically improve the problem-solving abilities of students